Initial experience with a PET/computed tomography system using silicon photomultiplier detectors. Issue 11 (November 2019) - Park, Sonya Youngju; Barrato, Lucia; Hatami, Negin; Davidzon, Guido; Gambhir, Sanjiv Sam; Iagaru, Andrei
Abstract : Purpose: A PET/computed tomography (CT) that uses silicon photomultiplier (SiPM) technology was installed at our institution. Here, we report the initial use of the new scanner and evaluate the image quality in comparison to standard PET/CT scanners. Procedures: Seventy-two patients were scanned first using standard PET/CT followed immediately by the new PET/CT system. Images from the new PET/CT system were reconstructed using a conventional [non time-of-flight (TOF)] algorithm, TOF alone and TOF in combination with BSREM. Images from standard PET/CT were reconstructed using clinical standard-of-care settings. Three blinded readers randomly reviewed four datasets (standard, non-TOF, TOF alone, TOF+BSREM) per patient for image quality using a five-point Likert scale. SUV measurements for the single most avid lesion on each dataset were also recorded. Results: Datasets from the new scanner had higher image quality ( P < 0.001) and SUV measurements ( P < 0.001) compared with the standard scanners, and scores further improved when TOF and BSREM algorithms were added (mean scores for standard, non-TOF, TOF alone and TOF+BSREM were 3.1, 3.9, 4.3 and 5.0, respectively; mean SUVmax for hottest lesion were 8.8, 10.3, 10.7 and 13.3, respectively). Conclusion: The SiPM-based PET/CT system outperforms two standard Bismuth germanium oxide- and Lutetium-yttrium oxyorthosilicate-based scanners in terms of image quality, with further benefits added using TOF and BSREM. This may be beneficial for detecting small lesions and more accurate disease staging. Abstract : Supplemental Digital Content is available in the text.